Rod ELLIS (Ed.). Becoming and Being an Applied Linguist. Amsterdam/ Philadelphia: John Benjamins Publishing Company, 2016. 373 pp. ISBN 978 90 272 1237 5 (HB) ISBN 978 90 272 1238 2 (PB) ISBN 978 90 272 6678 1 (E-Book) - Lopes, Ângela Filipe (Linguarum Arena, 2017)
.